The Bittersweet Truth: Corporate Social Responsibility in Online Communication Between a Coffee Company and its Customers - Ana Paula Kieling; Maria José Barbosa de Souza; Franciane Reinert Lyra; Ricardo Boeing (BBR: Brazilian Business Review)
With the increased use of the internet, social networks have acted as a relationship channel between consumers and companies. This paper aims to analyze the communication between an organization and its customers in a Brazilian online community, based on corporate social responsibility (CSR) criteria VBA model, which is composed of the elements of value, balance, and accountability. Netnography was applied to the Facebook fan page of a company brand that manufactures and sells coffee machines and capsules. The results demonstrated that the elements of the VBA model do not meet the expected criteria in the social network analyzed, showing a discrepancy between what the organization intends to deliver and what is delivered to customers. These findings have implications for the theory and practice of organizations, broadening the discussion about CSR practices and consumer behavior. It also highlighted the need to investigate deeply the constructs that built the VBA Model contributing to develop the field.